Testing hysteresis in a phillips-type aggregate wage equation: the case of Greece (1960-1999) - Παναγόπουλος, Γιάννης (SPOUDAI Journal of Economics and Business, 2000)
The main aim of this paper is the examination of the existence of the hysteresis effect in the Greek labour market, for a prolonged period of time (1960-1999). Therefore, alternative specifications of the hysteresis effect have been implemented into a Phillips -type aggregate wage equation of the Greek economy. The results favour the assumption that, at least for the examined specifications, hysteresis finds no statistical support. However, outside the strict aggregate wage equation framework there is some evidence of hysteresis. JEL Classification: J41